Clarity and Emotional Regulation as Protective Factors for Adolescent Well-Being: A Moderated Mediation Model Involving Depression - Jonathan Martínez-Líbano; María-Mercedes Yeomans-Cabrera; Axel Koch; Roberto Iturra Lara; Patrícia Torrijos Fincias (European Journal of Investigation in Health, Psychology and Education, 2025)
Introduction: Adolescent well-being is influenced by emotional regulation and clarity, particularly in contexts of depression, stress, and anxiety. Objective: This study explores how depression mediates the relationship between emotional regulation and well-being and whether emotional clarity moderates this interaction, providing a comprehensive model to understand adolescent mental health. Methodology: A cross-sectional study was conducted with 636 Chilean adolescents aged 10–18. Emotional clarity and regulation were assessed using the TMMS-24 scale, depression with the DASS-21 scale, and subjective well-being with the Personal Well-Being Index (PWI). Statistical analyses included descriptive statistics, Pearson correlations, and moderated mediation models (PROCESS Macro, Models 4 and 7). Results: Emotional regulation positively correlated with subjective well-being (r = 0.373, p < 0.01) and negatively with depression (r = −0.251, p < 0.01). Depression partially mediated the relationship between emotional regulation and well-being (B = 0.149, 95% CI [0.082, 0.225]), with regulation explaining 86.41% of the effect. Emotional clarity moderated the regulation-depression link, with higher clarity amplifying the protective impact of regulation (index = 0.008, 95% CI [0.0017, 0.0149]). Conclusions: Emotional regulation and clarity are vital for adolescent well-being and enhance the protective role of regulation against depression. Interventions targeting both constructs could improve mental health outcomes in vulnerable populations.